Studi Komparasi Jaminan Barang Bergerak Dan Tidak Bergerak Dalam Gadai Perspektif Hukum Islam Dan Hukum Perdata - Aji, Kurniawan; Anam, Syaiful; Fauzi, Rahman Ali (Ulumuna: Jurnal Studi Keilsman, 2021)
This paper is the result of a comparative study to answer the following problem formulations: First, how is the concept of guaranteeing movable and immovable property in pawning the perspective of Islamic law and civil law. Second, how are the similarities and differences in the concept of movable and immovable property guarantees in the perspective of Islamic law and civil law pawning. The type of research used is library. The research data was collected through the documentary method, namely by reading, recording, and collecting documents from several legal documents as well as the opinions of scholars and civil law experts that had been recorded relating to pawning law, especially to the object of pawn guarantees, which were then collected from the data. will be discussed and carried out comparative and qualitative analysis. These two methods are used to find conclusions from the similarities and differences between the two laws. The results of this study conclude that, the similarities between Islamic law and civil law are in a generality of the permissibility of pawn contracts and the terms of collateral. While the difference between the two laws lies in the object of the pledged collateral. In Islam, all goods, both movable and immovable, are included as collateral for pledges. Whereas in civil law, collateral for pledged goods is only limited to movable goods that can be used as collateral for pledges, in the case of immovable property it is called a mortgage, and immovable property, especially land, in civil law is called mortgage.